Writing history in Renaissance Italy: Leonardo Bruni and the uses of the past - Ianziti, Gary (I Tatti studies in Italian Renaissance history, 2012)
Bruni on writing history -- The Plutarchan option -- A new life of Cicero -- Between Livy and Polybius: Bruni on the first Punic War -- Genesis of the Florentine histories -- The Florentine histories: a sourcebook for statesmen -- Bruni and biography: a life of Aristotle -- Parallel lives: Dante and Petrarch -- Bruni, the Medici, and the Florentine histories -- The Florentine histories: from policy to propaganda -- A distant mirror: Athens, Sparta, and Thebes -- Memoirs of a humanist -- Writing from Procopius